Basics of Modeling the Probability of Corporate Borrowers’ Default - Ksenofontov, Alexander S.; Savon, Igor V.; Serba, Vladimir Y.; Shkurkin, Dmitry V. (International Journal of Economics and Financial Issues, 2016)
The paper has developed a set of evaluation models of the probability of corporate borrowers’ default, taking into account the macroeconomic and institutional factors on the example of the Russian construction industry companies. At the beginning of 2014, the lending volume of non-financial organizations was about 56% of the loan portfolio value and 39% of the value of the Russian banks’ assets. The paper has given a comparative analysis of approaches to modelling the probability of default and credit risk level, the results of which were used for the classification of the existing evaluation models of the probability of default, analyzing the advantages and disadvantages of each model class, including the degree of applicability for the Russian practice. The most risk-dominant figures, application of which allows to get more relevant models in the multi-factor analysis, were studied, and this helps create the relevant methodology of social development. Having been systematized and structured, various methodological aspects of estimation the probability of default helped form a complex attitude to the estimation methods of the probability of default, taking into account the advantages and disadvantages of these methods and the degree of their applicability for the Russian practice. Keywords: Default, risk-dominant figures, macroeconomics, corporate lending JEL Classifications: D81, G32